Small‐scale permeability heterogeneity has negligible effects on nutrient cycling in streambeds. Issue 6 (27th March 2013) - Bardini, L.; Boano, F.; Cardenas, M.B.; Sawyer, A.H.; Revelli, R.; Ridolfi, L.
Abstract : [1] Aquatic sediment hosts coupled pore water flow and biogeochemical reactions that mediate water quality across the fluvial corridor including adjacent alluvial aquifers. However, the effect of small‐scale variations in sediment hydraulic properties on nutrient transformation occurring within the sediment is poorly understood. We show through numerical flow and transport simulations, for two realistic heterogeneous permeability cases typical of lowland rivers and two idealized homogeneous ones, that there is little difference in the reactive transport fields, the bulk reaction rates, and nutrient sink/source function despite stark differences in flow fields. This is because the reactions are ultimately controlled by characteristic or bulk residence times that are similar for the heterogeneous and homogeneous cases. This is a promising result for predictive models based solely on relative ratios of residence times and reactive time scales. Key Points: Effect of permeability heterogeneity on nutrient dynamics is poorly understood Flow fields and nutrient concentration fronts in the streambed are simulated Sediment heterogeneity poorly affects streambed nutrient distribution